2014
DOI: 10.1111/cts.12247
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis to Assess the Impact of the CTSA on Biomedical Research Grant Collaboration

Abstract: Success of the Clinical Translational Science Award (CTSA) program implicitly demands team science efforts and well-orchestrated collaboration across the translational silos (T1-T4). Networks have proven to be useful abstractions of research collaborations. Networks provide novel system-level insights and exhibit marked changes in response to external interventions, making them potential evaluation tools that complement more traditional approaches. The present study is part of our ongoing efforts to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…Highly efficient networks strike a balance between functional segregation (eg, a unique strength of an individual CTSA institute) and global integration (eg, the communication structures and knowledge transfer among the institutes). Although the CTSA has more recently adopted the approach of network science with new language and hub-and-spoke models, the quantitative methods of network science have been applied rarely and only by individual CTSA institutes [15][16][17][18][19]. The current CTSA focus on developing common metrics should be complemented by consideration of the various properties of the nodes (ie, the individual CTSA institutes) and a quantitative definition of the links between them.…”
Section: Future Solutionsmentioning
confidence: 99%
“…Highly efficient networks strike a balance between functional segregation (eg, a unique strength of an individual CTSA institute) and global integration (eg, the communication structures and knowledge transfer among the institutes). Although the CTSA has more recently adopted the approach of network science with new language and hub-and-spoke models, the quantitative methods of network science have been applied rarely and only by individual CTSA institutes [15][16][17][18][19]. The current CTSA focus on developing common metrics should be complemented by consideration of the various properties of the nodes (ie, the individual CTSA institutes) and a quantitative definition of the links between them.…”
Section: Future Solutionsmentioning
confidence: 99%
“…However, our RNS results are in accordance with previous studies where an increasing trend in collaborations and team science efforts was found among the CTSA-affiliated investigators compared to pre- and post-CTSA funding. [17, 18] The RNS tools such as Harvard Profiles have been developed as valuable tools for evaluating changes in scientific collaborations over time. We have adopted Harvard Profiles open source software and used bibliometric data from it for the RNS analysis.…”
Section: Disscussionmentioning
confidence: 99%
“…Emerging as a strong interest among CTSAs, bibliometrics also prompted CTSA hubs to collaborate with librarians at their institutional health sciences or medical libraries for tracking publications, identifying bibliometric tools and resources, and investigating methods to use publication data for evaluating their progress. In addition, to assess the scope and impact of cross-disciplinary research collaboration, researchers have applied the theories and models of social network analysis (SNA) to analyze research grant data or grant and publication data together [18][19][20][21][22][23]. The adopted methods in previous studies focused on measuring the centrality of individual researcher or group in the cross-disciplinary research collaborations, the density of a research network, the strength of the collaborative relationships, the potential to bridge basic science researchers with clinical investigators, the detection of research communities, and the change of collaboration patterns.…”
Section: Introductionmentioning
confidence: 99%